Prevention of Corrupt Behavior through Assessment of the Work Behavior and Culture of Government Organizations - Rud Nokeo; Gayatri Indah (Asian Journal of Social and Humanities, 2024)
This study aims to determine the traits and behaviors that contribute to corruptive actions, as well as see opportunities for how they can be directed to the construction of different actions to show positive behavior. To see behavior so as not to overlap, a more in-depth study was also carried out regarding organizational culture (Hofstede, 2001) to control and become the scope of government organizations. This research uses a qualitative descriptive method with a descriptive approach to understand, explain, and interpret facts, phenomena, and events. The results of this study will later be used as a predictor in the development of behavioral assessment instruments against corrupt acts and employee development based on behavioral characteristics and government organizational culture. On acts of corruption and also support organizational cultural characteristics that can direct these traits and characters to positive behavior. It can be used as a reference to manage one's character and behavior so as not to lead to corruptive actions.